(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides data on the harmfulness, distribution and lifestyle of the whitefly, which in recent years has been a harmful object in our republic. In order to determine the effectiveness of insecticides against whitefly, observational studies based on tomato pheromones were first introduced. On this basis, in three variants, tests were carried out on the preparations Meteorite 50% h.d. 0.1 - 0.125 kg / ha., (Reference) bestseller 10% ae. 0.2 kg / ha. The highest efficiency was observed in the variant where the Meteorite 50% EH was used. 0.1 - 0.125 kg / ha. In this variant, the efficiency was 7-day 80.3-85.5%.